Targeting PI3K/Akt/mTOR Signaling in Cancer - Porta, Camillo; Paglino, Chiara; Mosca, Alessandra (Frontiers in Oncology, 2014)
The phosphatidylinositol-3-kinase (PI3K)/Akt and the mammalian target of Rapamycin (mTOR) signaling pathways are two pathways crucial to many aspects of cell growth and survival, in physiological as well as in pathological conditions (e.g. cancer). Indeed, they are so interconnected that, in a certain sense, they could be regarded as a single, unique pathway. In this paper, after a general overview of the biological significance and the main components of these pathways, we address the present status of the development of specific PI3K, Akt and mTOR inhibitors, from already registered medicines to novel compounds that are just leaving the laboratory bench.